2019
DOI: 10.3390/ijms20081989
|View full text |Cite
|
Sign up to set email alerts
|

CaDHN5, a Dehydrin Gene from Pepper, Plays an Important Role in Salt and Osmotic Stress Responses

Abstract: Dehydrins (DHNs), as a sub-family of group two late embryogenesis-abundant (LEA) proteins, have attracted considerable interest owing to their functions in enhancing abiotic stress tolerance in plants. Our previous study showed that the expression of CaDHN5 (a dehydrin gene from pepper) is strongly induced by salt and osmotic stresses, but its function was not clear. To understand the function of CaDHN5 in the abiotic stress responses, we produced pepper (Capsicum annuum L.) plants, in which CaDHN5 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Luo et al [26] showed that Arabidopsis plants overexpressing a SKn-type dehydrin from Capsicum annuum L. ( CaDHN5 ) resulted an increased tolerance to salt and osmotic stress, suggesting an important role for CaDHN5 in response to the mentioned abiotic stresses [26]. In addition, using VIGS (virus-induced gene silencing) technique, the authors reported that knockdown of the CaDHN5 gen suppressed the expression of manganese superoxide dismutase ( MnSOD ) and peroxidase ( POD ) genes in transformed pepper plants [26]. These changes caused a higher oxidative stress in the VIGS lines than in control pepper plants under NaCl or osmotic stress conditions, as observed by the data of some stress-oxidative parameters (superoxide accumulation, lipid peroxidation, and electrolyte leakage), chlorophyll levels, and the rate of water loss.…”
Section: Biostimulants and Salt-stress Responsementioning
confidence: 99%
See 1 more Smart Citation
“…Luo et al [26] showed that Arabidopsis plants overexpressing a SKn-type dehydrin from Capsicum annuum L. ( CaDHN5 ) resulted an increased tolerance to salt and osmotic stress, suggesting an important role for CaDHN5 in response to the mentioned abiotic stresses [26]. In addition, using VIGS (virus-induced gene silencing) technique, the authors reported that knockdown of the CaDHN5 gen suppressed the expression of manganese superoxide dismutase ( MnSOD ) and peroxidase ( POD ) genes in transformed pepper plants [26]. These changes caused a higher oxidative stress in the VIGS lines than in control pepper plants under NaCl or osmotic stress conditions, as observed by the data of some stress-oxidative parameters (superoxide accumulation, lipid peroxidation, and electrolyte leakage), chlorophyll levels, and the rate of water loss.…”
Section: Biostimulants and Salt-stress Responsementioning
confidence: 99%
“…These changes caused a higher oxidative stress in the VIGS lines than in control pepper plants under NaCl or osmotic stress conditions, as observed by the data of some stress-oxidative parameters (superoxide accumulation, lipid peroxidation, and electrolyte leakage), chlorophyll levels, and the rate of water loss. The results demonstrated an important role for the CaDHN5 gene in the tolerance of plants to salt and osmotic stresses as well as in the salt and osmotic stress signalling pathways [26]. The results also indicated that CaDHN5 positively regulates the expression of the MnSOD and POD genes, but also other stress-related genes, including AtSOD1 (encoding a H + /Na + plasma membrane antiporter), AtDREB2A (a transcription factor in the ABA signalling pathway), and AtRSA1 and AtRITF1 genes that regulate the transcription of several ROS scavenging-related genes and the AtSOS1 gene [26].…”
Section: Biostimulants and Salt-stress Responsementioning
confidence: 99%
“…Dehydrins are involved in protection against oxidative stress by reducing H 2 O 2 levels and enhancing the expression of ROS scavenging enzymes [70]. Conversely, suppressed expression of ROS scavenging enzymes, including superoxide dismutase and peroxidase, leading to ROS accumulation was reported in dehydrin-silenced pepper plants [71]. In this context, the link between dehydrins and ROS warrants further research.…”
Section: Discussionmentioning
confidence: 96%
“…Dehydrins were reported to have the function of binding DNA to protect DNA from damage caused by environmental stress. Thus far, some studies have reported that DHN proteins can bind to DNA, the Vitis riparia dehydrin locates in the nucleus and binds to DNA to protect it from hydrogen peroxide [ 24 ]. Given that the four LkDHNs could bind the dsDNAs and present in both the nucleus and cytoplasm, it is possible that these LkDHNs were located in the nucleus to protect the DNA from oxidative stress.…”
Section: Discussionmentioning
confidence: 99%